Cidade e turismo: o imaginário de Nova York na Revista Viagem e Turismo - Bandeira, Milena Berthier (My University, 2014)
This research brings together a theorical construction on the City, from authors such as Barbara Freitag, Henri Lefebvre, Lewis Mumford, Massimo Canevacci, Susana Gastal, among and others, bringing it closer to another theorycal body theory, the one built around the question of Imaginary. The objective is to evaluate how the Imaginary City, present in this midia specialized in Tourism, contribute to on building the Imaginary of tourist city, especially on appropriation and re-signification the idea of paradise. For analysis were listed among the 120 editions of the magazine Viagem e Turismo to those which brought in its cover some urban tourist destinations. The research follows of the Content Analysis of Laurence Bardin, from which had emerged the categories Excess, Maze, Sin, Forbidden, associated to the Imaginary City and Paradise, Sacred, Nature, Landscape associated to the Imaginary Tourism. Applied to the categories, it appears that the Imaginary of the City, associated with the excesses, mazes, sins and banned, historically buit is reproduced in the contemporary press practices, disqualifies the space City for Tourism. The research suggests discussing the concept of Tourism so that from it there will be a redemption of self-esteem for the City and, consequently, an imaginary res-signification of the City for Tourism.
A presente pesquisa reúne uma construção teórica sobre a Cidade a partir de autores como Bárbara Freitag, Henri Lefebvre, Lewis Mumford, Massimo Canevacci, Susana Gastal, entre outros, para aproximá-la de outro corpo teórico, aquele construído em torno da questão do Imaginário. O objetivo é avaliar como os imaginários urbanos, presentes na mídia especializada em Turismo, contribuem para a construção do Imaginário cidade turística, em especial na apropriação e ressignificação da idéia de paraíso. Para a análise, foram elencadas, entre as 120 edições da revista Viagem e Turismo, aquelas que apresentaram em sua capa destinos turísticos urbanos. A pesquisa se deu à luz da Análise de Conteúdo de Laurence Bardin, da qual emergiram as categorias Excessos, Labirinto, Pecado, Interdito (associadas ao Imaginário da Cidade) e Paraíso, Sagrado, Natureza, Paisagem (associadas ao Imaginário do Turismo). Aplicadas às categorias, constata-se que o Imaginário da Cidade, associado aos excessos, labirintos, pecados e interditos, construído historicamente, é reproduzido nas práticas da imprensa especializada contemporânea, desqualificando o espaço Cidade para o Turismo. A pesquisa propõe o debate do conceito de Turismo para que a partir dele haja um resgate da auto-estima da Cidade e, por conseqüência, uma ressignificação do Imaginário da Cidade para o Turismo.
Keywords: Turismo; Turismo; Turismo urbano; Cidades; Imaginário; Imaginário da cidade; Tourism; Urban tourism; Cities; Imaginary; City´s imaginary